Role of Premycofactocin Synthase in Growth, Microaerophilic Adaptation, and Metabolism of Mycobacterium tuberculosis - Gopinath Krishnamoorthy (American Society for Microbiology, 2021)
ABSTRACT Mycofactocin is a new class of peptide-derived redox cofactors present in a selected group of bacteria including Mycobacterium tuberculosis. Mycofactocin biosynthesis requires at least six genes, including mftD, encoding putative lactate dehydrogenase, which catalyzes the penultimate biosynthetic step. Cellular functions remained unknown until recent reports on the significance of mycofactocin in primary alcohol metabolism. Here, we show that mftD transcript levels were increased in hypoxia-adapted M. tuberculosis; however, mftD functionality was found likely dispensable for l-lactate metabolism. Targeted deletion of mftD reduced the survival of M. tuberculosis in in vitro and in vivo hypoxia models but increased the bacterial growth in glucose-containing broth as well as in the lungs and spleens, albeit modestly, of aerosol-infected C57BL/6J mice. The cause of this growth advantage remains unestablished; however, the mftD-deficient M. tuberculosis strain had reduced NAD(H)/NADP(H) levels and glucose-6-phosphate dehydrogenase activity with no impairment in phthiocerol dimycocerosate lipid synthesis. An ultrastructural examination of parental and mycofactocin biosynthesis gene mutants in M. tuberculosis, M. marinum, and M. smegmatis showed no altered cell morphology and size except the presence of outer membrane-bound fibril-like features only in a mutant subpopulation. A cell surface-protein analysis of M. smegmatis mycofactocin biosynthesis mutants with trypsin revealed differential abundances of a subset of proteins that are known to interact with mycofactocin and their homologs that can enhance protein aggregation or amyloid-like fibrils in riboflavin-starved eukaryotic cells. In sum, phenotypic analyses of the mutant strain implicate the significance of MftD/mycofactocin in M. tuberculosis growth and persistence in its host. IMPORTANCE Characterization of proteins with unknown functions is a critical research priority as the intracellular growth and metabolic state of Mycobacterium tuberculosis, the causative agent of tuberculosis, remain poorly understood. Mycofactocin is a peptide-derived redox cofactor present in almost all mycobacterial species; however, its functional relevance in M. tuberculosis pathogenesis and host survival has never been studied experimentally. In this study, we examine the phenotypes of an M. tuberculosis mutant strain lacking a key mycofactocin biosynthesis gene in in vitro and disease-relevant mouse models. Our results pinpoint the multifaceted role of mycofactocin in M. tuberculosis growth, hypoxia adaptation, glucose metabolism, and redox homeostasis. This evidence strongly implies that mycofactocin could fulfill specialized biochemical functions that increase the survival fitness of mycobacteria within their specific niche.